2011
DOI: 10.1093/brain/awr193
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of astrocyte–motoneuron cross-talk in mutant superoxide dismutase 1-related amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis is a neurodegenerative disease in which death of motoneurons leads to progressive failure of the neuromuscular system resulting in death frequently within 2-3 years of symptom onset. Focal onset and propagation of the disease symptoms to contiguous motoneuron groups is a striking feature of the human disease progression. Recent work, using mutant superoxide dismutase 1 murine models and in vitro culture systems has indicated that astrocytes are likely to contribute to the propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
187
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(203 citation statements)
references
References 47 publications
12
187
0
4
Order By: Relevance
“…Specifically, we found elevated glycogen in gray and ventral white matter samples from autopsied patients with ALS, confirmed by histological analyses showing elevated glycogen in both neurons and glia. The increased glycogen in the CNS of SOD1 G93A mice and humans with ALS is consistent with spinal cord gene expression profiling studies from ALS mice and humans that showed elevated glycogen synthase mRNA levels and altered α-glucosidase mRNA (13,19). Indeed, we show here that lysosomal (glycogen degrading) α-glucosidase activity is significantly reduced within the lumbar spinal cord of SOD1 G93A mice in advance of the onset of hindlimb paralysis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Specifically, we found elevated glycogen in gray and ventral white matter samples from autopsied patients with ALS, confirmed by histological analyses showing elevated glycogen in both neurons and glia. The increased glycogen in the CNS of SOD1 G93A mice and humans with ALS is consistent with spinal cord gene expression profiling studies from ALS mice and humans that showed elevated glycogen synthase mRNA levels and altered α-glucosidase mRNA (13,19). Indeed, we show here that lysosomal (glycogen degrading) α-glucosidase activity is significantly reduced within the lumbar spinal cord of SOD1 G93A mice in advance of the onset of hindlimb paralysis.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, glucose uptake and/or levels within the CNS are significantly diminished in patients with ALS (37), SOD1 G93A mice (32,38), and in WT mice exposed to cerebrospinal fluid (CSF) from patients with ALS (39). Moreover, lactate levels are reduced in spinal cords of SOD1 G93A mice (19), as is the expression of MCT1 (36). Our results extend these findings.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The physiopathological complexity that characterizes ALS [5,6] is one of the most limiting factors for the development of successful therapies. Several works have been conducted targeting one or more of the physiopathological mechanisms linked to the disease, but even if they achieved positive experimental results they have failed to translate into successful human therapies [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…It is also of relevance that alterations of the SOD1 protein have been reported in sporadic ALS patients [4], increasing the interest of this murine model. Several mechanisms have been implicated as contributors to MN death in ALS, such as glutamate excitotoxicity, oxidative stress, protein misfolding, mitochondrial defects, impaired axonal transport, and inflammation [5,6]. Nevertheless, positive experimental results targeting some of these abnormalities have failed to translate into successful human trials [7,8].…”
Section: Introductionmentioning
confidence: 99%